STUDI KOMPARATIF PENGARUH INTELLECTUAL CAPITAL TERHADAP TAX AVOIDANCE PADA PERUSAHAAN DOMESTIK DAN PERUSAHAAN MULTINASIONAL - Dodi Prasetya; Lintang Venusita (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
This study aimed to examine the effect of intellecual capital on tax avoidance in both domestic and multinational companies in Indonesia, and to examine whether there are differences in both effect or not. The sample in this study consisted of 100 domestic manufacturing companies and 100 of multinational manufacturing companies registered in Indonesia Stock Exchange from 2019-2022. This type of research is quantitative study using stratified random sampling with multiple linear regression analysis models that are processed using SPSS 23. The results of this study show that Intellecual capital has an effect on tax avoidance both in domestic and multinational companies. So it can be concluded that there is no difference in the effect of intellecual capital on tax avoidance in domestic and multinational companies.